The application of systematic conservation planning in the succulent Karoo biome of South Africa - Desmet, Philip George (Department of Biological Sciences, 2017)
Systematic conservation planning is about making spatially explicit decisions regarding the use of land, based on the observed or expected biodiversity present at a site and the potential for that same site to support alternative /and-uses that are not compatible with the persistence of biodiversity. This thesis examines three questions relating to the application of systematic conservation planning: Which biodiversity surrogates should be used in Namaqualand to do systematic conservation plans? How should targets be set for these surrogates? How can this information be integrated and used within a systematic conservation planning framework? Comparing how well different biodiversity surrogates achieved a set of targets illustrated that continuous biodiversity data (i.e. vegetation types and land-classes) perform better as surrogates than point-based species distribution data. Quarter degree square-based species distribution data cannot be used for on-the-ground conservation planning. It was demonstrated that it is possible to set biologically meaningful conservation targets to represent biodiversity pattern in land classes by applying the Species Area Relationship and using plot-based survey data. The method developed here has the potential to revolutionise conservation planning as it provides for the first time a defensible means for setting representation targets for land classes that are grounded on ecological theory and that use real data. The thesis also explores the potential for metapopulation and fragmentation studies to provide useful insights into developing targets for ecological processes by relating the amount of remaining habitat to key thresholds in probability of population persistence. Two examples, at different spatial scales (1:10 000 and 1:100 000), are used to illustrate how different biodiversity information can be integrated and used within a systematic conservation planning framework. At the finer scale biodiversity and land-use data are 3 used to set priorities for the development of a statutory reserve in the Knersvlakte region of the Succulent Karoo using cadastres as planning units. At the larger scale the data are used in the same region to design a biosphere reserve that promotes the persistence of ecological processes in the landscape using gridded planning units. Both studies use the C-Plan software to assist in the planning and design process. A lesson from both these studies is that there needs to be a paradigm shift in conservation from an on/off reserve mindset to a more integrative whole landscape mindset.